Plata v. Brown and Realignment: Jails, Prisons, Courts, and Politics - Schlanger, Margo (2013)
The year 2011 marked an important milestone in American institutional reform litigation. That year, a bare majority of the U.S. Supreme Court, in an opinion in Brown v. Plata by Justice Anthony Kennedy, affirmed a district court order requiring California to remedy its longstanding constitutional deficits in prison medical and mental health care by reducing prison crowding. Not since 1978 had the Court ratified a lower court's crowding-related order in a jail or prison case, and the order before the Court in 2011 was fairly aggressive; theoretically, it could have (although this was never a real prospect) induced the release of tens of thousands of sentenced prisoners or the expenditure of billions of dollars in new prison construction. This Article explores pertinent features of the relevant legal and political ecosystem in which these changes are taking place. Informed by court documents, state reports and policy papers, and interviews, I trace the litigation and policy that led to and that have followed the Supreme Court's ruling affirming the Plata/Coleman population order. The result illustrates the complex interplay of institutional reform litigation and political outcomes and processes. The Article proceeds in four parts. Part I sets out crucial background about how a 1996 anti-prisoners'-rights federal statute, the Prison Litigation Reform Act (PLRA), structures correctional civil rights litigation. Part II paints the relevant history of Plata and Coleman, in the district court and the Supreme Court, focusing on the interaction of court procedure and politics-describing, for example, how the litigation promoted a more explicit, open, and elaborate multiparty bargaining process over prison population and criminal justice policy; and how the focus during trial on public safety actually increased prisoners' rights advocates' effectiveness outside of litigation. It analyzes Governor Jerry Brown's realignment plan - the state's response to the Plata/Coleman population order, which shrinks the parole population and shortens parole-revocation sentence terms, moves some classes of prisoners from state to county custody, and encourages counties to consider nonincarcerative penalties for crime. Part III looks at one of the key features of the environment in which realignment is being implemented: pre-PLRA population court orders. I demonstrate that contrary to Justice Scalia's rhetoric, population orders such as the Plata/Coleman order have been very common in correctional civil rights cases; in fact, some of these run-of-the-mill population orders are vital parts of the ongoing story of California prison reform. In California, the existing jail population orders, and the mindset that accompanies them, are encapsulated by two (equivalent) rules of thumb - One prisoner, one bed, and No floor sleepers. Currently covering about a third of California's jails and jail population, these orders have functioned for decades as county-specific bail and jail sentencing reform mechanisms. Part IV concludes by examining the prospects of a litigation-focused response to what I call the hydra risk - the very real possibility that Plata and Coleman could succeed at chopping the head off of unconstitutional conditions of prison confinement in California, only to cause fifty-eight counties to develop unconstitutional conditions of jail confinement